Evaluation of ecotypes of long pepper - Riya Joseph (Department of Plantation Crops and Spices, College of Horticulture, 2008)
Investigations on “Evaluation of ecotypes of long pepper (Piper longum L.) was undertaken at the Department of Plantation Crops and Spices at College of Horticulture, Vellanikkara during the period 2005-2007.The major objective of the study was to evaluate various ecotypes of Piper longum available at the Department of Plantation Crops and Spices for their variability in yield, morphological and biochemical characters so as to identify the superior types. Twenty accessions genetically catalogued and studied for their variability in vegetative, reproductive and biochemical characters and found that all the accessions varied with respect to these characters.